The Relationship Between a Linear Equations System of COVID-19 and the Faithfulness to Allah SWT - Ezra Efrizardi Yusufa (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2021)
In Islam, mathematics can be used and applied in worship and muamalah. One of them is a system of linear equations. The Corona Virus Disease pandemic or better known as the COVID-19 is a disease that still be pandemic in every country. A person’s devotion of Allah SWT can be influenced by an event. In this study, we will present the relationship between system of linear equations in the COVID-19 case and person’s devotion of Allah SWT. Using exponential functions of linear equation system which describes the number of victims exposed to COVID-19, we will show that the higher the number of victims exposed to COVID-19 outbreak from day to day, it will increase one's devotion to Allah SWT. And the lower the number of victims exposed to COVID-19 outbreak from day to day, all people must not be careless and continue to increase their devotion to Allah SWT.